2017
DOI: 10.1159/000455148
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukaemia/ Small-Cell Lymphocytic Lymphoma of the Lacrimal Sac: A Case Series

Abstract: Background: Lymphomas of the lacrimal sac are rare, accounting for less than 10% of lacrimal sac malignant tumours. They may present with symptoms typical of secondary acquired nasolacrimal duct obstruction and are thus often misdiagnosed. Methods: Case series and literature review. Results: Herein we describe 3 cases of chronic lymphocytic leukaemia (CLL)/small-cell lymphocytic lymphoma (SLL) of the lacrimal sac with immunohistochemical and in 1 case molecular confirmation. Conclusion: Lymphomas of the lacrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…Enlargement of the lacrimal ducts and surrounding bone compression could also be observed. Though not as commonly as in epithelial malignancies, bony destruction could be observed in LSLs [25] . MRI is more helpful in the differential diagnosis of LSTs since MRI could provide better tumor definition and determination of the cystic or solid nature of the masses.…”
Section: Discussionmentioning
confidence: 89%
“…Enlargement of the lacrimal ducts and surrounding bone compression could also be observed. Though not as commonly as in epithelial malignancies, bony destruction could be observed in LSLs [25] . MRI is more helpful in the differential diagnosis of LSTs since MRI could provide better tumor definition and determination of the cystic or solid nature of the masses.…”
Section: Discussionmentioning
confidence: 89%
“…They present with symptoms of dacryocystitis and epiphora. There are reports which describe 3 lacrimal sac Leukaemia/Small-Cell Lymphocytic Lymphoma cases [19]. Some authors found only 3 cases of adenocarcinoma among 74 malignant lacrimal sac tumors, and others reported 4 adenocarcinomas among 115 lacrimal sac neoplasms [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…TA is an uncommon lesion, with a prevalence of 0.056 to 0.03 in every 1000 births, described as a single arterial stem emerging from the heart, which in turn gives rise to the pulmonary trunk in various ways. [4][5][6][7][8] TA belongs to the group of ectomesenchymal tissue migration anomalies caused by the aberrant migration of neural crest cells through the branchial arch vessels during cardiogenesis. 9,10 Chromosomal abnormalities are detectable in 8.7% of cases of TA.…”
Section: Discussionmentioning
confidence: 99%